TINDAK PIDANA TERORISME OLEH ANGGOTA JAMAAH ISLAMIYAH DAN ANGGOTA MAJELIS MUJAHIDIN INDONESIA DALAM PERSPEKTIF KRIMINOLOGI - Faradilla, Citra; Kana, Philips A. (LPPM Universitas Ekasakti Padang, 2019)
Terorism in Indonesian is regulated constitution number 15th 2003 about stipulation of government regulations in lieu of laws number 1st 2002 about eradication of terrorist. Although, constitution eradication of terrorist has been formed, terrorism in Indonesian always happened, like as terrorist act at J.W. Marriot Hotels on 2003 whom responsible was Noordin M.Top dan Dr. Azahari Husin. They were join in Jamaah Islamiyah organization. Based on the above rationale , the issues discussed , namely , first, what is factor cause incidence terorism by members of Jamaah Islamiyah and Majelis Mujahidin Indonesia? second, How is effort Indonesian Republic of Police to prevent incident terorism? Spesification research is analytical descriptive. Method used is as a normative juridical approach and empirical as the main supporter of the main approache. Data source use of primary data and secondary data. Engineering is a field study data collection through interviews and literature study. Data were presented in the form of descriptive analysis, which describes factor cause incidence terorism and effort to prevent incident terorism by of Jamaah Islamiyah and Majelis Mujahidin Indonesia, while after analysis data will presented with qualitative method. Based on the results of research and discussion can be deduced, first, factor cause incidence terorism by members of Jamaah Islamiyah and Majelis Mujahidin Indonesia because mindset about Islam religion which wrong, social public relation, social politic factor, economic factor and then Solidarity religion. Second, effort Indonesian Republic of Police to prevent incident terorism, from Regional police West Sumatera which is conducted by Intelijen Directory as implement the program Intelijen Directory to prevent incident terorism, to do coordination with others side, data collection and protection for Electronic media, Deradicalization and Mapin, Fublic Founding Directory as improve quality person of Indonesian Republic Police and arrangement person, external coordination, judge communication with society, counseling and founding for society and Public Relation Section as submit information to society and be relation between Police with society.